Practice Of Using Interactive Multimedia In Improving Fiqih Learning Outcomes - Raudhatul Fuad; Dhiauddin Dhiauddin; Saifuddin Saifuddin (PT. Anagata Sembagi Education, 2025)
This study aims to examine the implementation of interactive multimedia in Fiqh learning at MIN 13 Pidie Jaya. Using a qualitative descriptive method, this study explores information through data triangulation including observation, interviews, and documentation. The results of the study indicate that the use of interactive multimedia in Fiqh learning has a significant impact on the learning process and outcomes of students. Interactive multimedia makes Fiqh learning, which was previously considered monotonous, more interesting and enjoyable. The role of teachers in the implementation of interactive multimedia is very strategic, namely as learning designers, facilitators, motivators, evaluators, and technical assistants. Through interactive multimedia, students are more motivated, actively participate, and show an increase in understanding of complex Fiqh concepts. This study recommends the need for improved technology infrastructure, ongoing training for teachers, selection of appropriate media, periodic evaluation, and collaboration with parents to optimize the use of interactive multimedia in Fiqh learning